Th17 cells and their cytokines serve as potential therapeutic target in experimental autoimmune neuritis - Shuping Liu (Brain and Behavior, 2019)
Abstract Background Accumulating evidence has pointed that T helper 17 cells and their cytokines are pathogenic in Guillain–Barré syndrome (GBS). However, little is known concerning the IL‐17 expression change trend during the whole course of disease, and whether drugs specially targeting Th17 cells or their cytokines have potential effects on experimental autoimmune neuritis (EAN) is uncertain. Methods We explored the IL‐17 and receptor‐related orphan receptor‐gamma‐t (RORγt) expression change trends in EAN rats to identify the stage of effect of Th17 pathway in EAN, and further, we investigated the effect of RORγt inhibitors by assessing clinical score, histological staining, and IL‐17 and RORγt expression change trends in serum and tissues. Results The expression level of IL‐17 and RORγt in serum and tissues increased with the progression of the disease in the EAN group and decreased after the disease reaching its peak. RORγt‐IN‐1 treatment strikingly reduced the neurological deficits by ameliorating inflammatory cell infiltration, deceased the serum IL‐17 and RORγt levels, and further downregulated the expression of IL‐17 and RORγt mRNA in spleen, lymphnodes, and sciatic nerve. Conclusions Th17 cells and their cytokines are closely associated with the onset of GBS and the novel RORγt inhibitors may be prospective strategies in treating GBS.